Factors influencing the perception of stress among patients with chronic illnesses - Parvin, Masuma; Keya, Mahbuba Kaniz (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study examined the influence of age, gender, education and monthly income on perceived stress of type-2 diabetes and coronary heart disease patients. The study was conducted on 100 chronic patients (50 diabetic and 50 coronary heart disease) selected randomly from six hospitals and clinics of Rajshahi city in Bangladesh. The age range of sample was 35 to 65 years (M=53.03, SD=8.597). All of the participants were out-patients. Perceived Stress Questionnaire (Keya, 2006) was used to assess the stress level. The t- test analyses revealed that female patients perceive high level of stress than male patients. Results of the analysis of variance revealed that the main effect of education on perceived stress was statistically significant, illiterate patients perceived high level of stress compare to primary, secondary, higher secondary and graduate group. Regression analysis revealed that demographic variables (age, gender and monthly income) explained 26.8 percent of the variance that highlighting contributions to patients’ perceived stress. The findings conclude that gender, monthly income and level of education have significant effects on patients’ perceived stress.